Modelagem do deslocamento de uma coluna de perfuração imersa em leito de cascalhos - Miyoshi, Maryelen Hissae (2020)
Investment in new technologies for the exploration of oil reservoirs in challenging scenarios is growing in the oil and gas industry. One of the techniques that has been widely used for the construction of oil wells in adverse environmental conditions is the directional drilling. However, the construction of wells in ultra-deep waters makes this activity extremely costly. In this scenario, any operational problem during the drilling process is responsible for increasing project costs or even making it unfeasible. Among the most common operational problems is the mechanical stuck of the drill string. The problem occurs when a cuttings bed is formed inside the well. The presence of the cuttings bed can cause increased frictional forces during pull out of hole operation, which can damage the equipment and lead to mechanical stuck of drill string. Although the stuck of the drill string inside the well is a usual problem, there is still no effective solution to prevent its occurrence. Currently, stuck detection is carried out by monitoring parameters such as the drag force. Therefore, the objective of this work is to model the forces acting on drill string assembly during the pull out of hole. Such forces arise from the interaction between equipment, cuttings bed, fluid and well wall. The model is based on lumped mass and momentum conservation equations and the forces due to cuttings bed are determined using theories of granular flow. The studied cuttings bed is composed of spherical glass particles and the fluid used is water. The forces calculated by the model showed a similar trend to that observed experimentally for different drill pipe velocities, cuttings bed heights and drill bit areas. In addition, the model proved to be able to calculate the cases whether there would be a plug formation or not. The sensitivity analysis of the model revealed that the angle of repose of the cuttings pile influences the time required for the formation of the plug, while the friction coefficient adopted impacts the magnitude of the calculated forces. Finally, a case study was carried out coupling the proposed model to an existing drag model, in which potential contributions from the use of the proposed modeling were identified to detect field problems.